Mathematical and Computer Simulation of the Process of Movement of Respirable Dust Particles in the Working Area - Lashko, Yevhenii; Chencheva, Olha; Laktionov, Ivan; Rieznik, Dmytro; Halchenko, Nadia (Baltic Journal of Modern Computing, 2024)
Most air purification systems are formed on the basis of the "modular principle" using a waste-free production scheme, standardized dust collection equipment and ventilation systems. The disadvantages of such a complex, which is assembled from heterogeneous purification equipment, are the large overall dimensions of the devices, low individual performance and low gas flow rates in the devices, which limit the ability to purify large volumes of air, and therefore the task of preliminary verification of their capabilities arises. Modern computer simulation software makes it possible to study the movement of microscopic particles and determine the stable patterns of this process. This study focuses on the mathematical and computer simulation of the process of movement of respirable dust particles in the working area, based on the principles of designing efficient modular devices that maximize the use of centrifugal force to improve the performance of dust and gas cleaning equipment. The object of study is the proposed air purification device as a separate part of the overall purification complex. The subject of the study is computer simulation of the movement of dust particles in the air flow. The scientific and practical value of the research results is that for the first time the regularities of aerodynamic processes occurring in the cylindrical body of the "centrifugation module" were determined, which were obtained by mathematical and computer simulation methods, which confirms the effectiveness of air purification by the proposed device and makes it possible to introduce it into mass production.